Partial Exchange Transfusion in the Management of a Preterm Neonate with Severe Anaemia from Acute Foetomaternal Haemorrhage: A Case Report - Basany Laxman; Batthula Vinay; Gandrakota Naga Priyanka; Giddaluru Rao Priyanka (Journal of Clinical and Diagnostic Research, 2024)
Foetomaternal Haemorrhage (FMH) refers to the passage of foetal blood into the maternal circulation. FMH is rarely diagnosed antenatally as clinical findings are subtle and non specific. Massive FMH is suspected when foetal movements are decreased, and Cardiotocographic (CTG) findings are abnormal with decreased heart rate variability, saw-tooth or a sinusoidal pattern. Massive FMH can lead to foetal demise, stillbirth, hydrops, or the birth of a severely anaemic infant with hypovolaemic shock. A 35-week pregnant woman presented with decreased foetal movements, and an emergency caesarean section was performed due to late deceleration on the cardiotocograph. The baby was very pale at birth and in shock. The Kleihauer-Betke (KB) test performed on the mother’s blood shortly after delivery showed 2.7% foetal red cells, suggesting 135 cc of FMH. The clinical features and outcome of FMH depend on the gestational age, volume, and rapidity of FMH, as well as, whether it is acute or chronic. Packed cell transfusion is recommended, but in babies with severe anaemia and cardiac failure, partial exchange transfusion is performed. The baby was managed with a fluid bolus, inotropic support, respiratory support, and partial exchange transfusion, resulting in a successful outcome. A high index of suspicion enables the obstetrician to undertake diagnostic tests, cordocentesis, plan for intrauterine transfusion or delivery, and alert the neonatal team for a better outcome.